Enhancing Performance Production Forest Inventory in Java Using LiDAR Technology - Hartanto, Rachmat Pudjo; Kusmana, Cecep; Nugroho, Naresworo (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Forest inventory (FI) is an essential process for assessing the quality and quantity of forest resources, forming the foundation for strategic planning and sustainable management. Terrestrial methods (sampling / census), remote sensing methods, or a combination of these can be used to obtain this data and information. This study explores the application of LiDAR technology to improve forest inventory practices in plantation forests (teak and pine) in Java, Indonesia. LiDAR sensors, deployed via drones and handheld devices, were tested in several Perum Perhutani Forest Management Unit compartments, which were the locations of proof of concept (PoC). PoC is a testing process to prove the feasibility of a concept or methodology before it is implemented. The results showed that LiDAR-based inventories provide superior accuracy compared to traditional methods, with data showing strong alignment with ground-truth measurements. These results underscore the potential of LiDAR technology to revolutionize FI practices and inform sustainable forest management strategies in Java and beyond. The use of this technology in natural forests where the variety of tree species is more diverse certainly requires further study.